A Statistical Approach to Quantify Atmospheric Contributions to the ITEC WN4 Structure Over Low Latitudes. Issue 3 (20th March 2019) - Chen, T.; Wan, W.; Xiong, J.; Yu, Y.; Ren, Z.; Yue, X.
Abstract: Based on multiyear observations of ionospheric total electron content (TEC) and atmospheric wind, we develop a new method to interpret the atmospheric contribution to the ionospheric wave number‐4 (WN4) structure according to their coherences in annual variations. First, the ionospheric WN4 is extracted from the equatorial integrated TEC (ITEC) using the global ionospheric maps. The wind observation from the TIMED Doppler Interferometer on board the Thermosphere Ionosphere Mesosphere Energetic and Dynamics (TIMED) satellite are used to deduce the latitudinal symmetric and antisymmetric components of the zonal and meridional DE3 (diurnal, eastward, and zonal wave number 3), SE2 (semidiurnal, eastward, and zonal wave number 2), and SPW4 (stationary planetary wave with zonal wave number 4). We then develop a regression model to estimate the coupling efficiency, the background diurnal influence, and the associated contribution in ITEC WN4. (1) The zonal symmetric DE3 is the most efficient tide in generating ITEC WN4, while the zonal symmetric SPW4 plays a secondary but varied role. (2) The diurnal variation of background ionosphere/thermosphere influence's amplitude is similar to that of the zonal mean ITEC during the day, with a westward phase velocity. (3) The zonal symmetric DE3 resulted WN4 can reach 7% of the zonal daily mean ITEC, while the observed total WN4 value is about 10%. The contributions by the zonal symmetric SE2, SPW4, and meridional symmetric SE2 are comparable with respective maxima 1.5% of the zonal daily mean ITEC. The present results confirm former suggestions that symmetric zonal DE3 is the primary source for ionospheric WN4, and the contributions due to antisymmetric wind components are relatively small in ITEC WN4. Plain Language Summary: The ionosphere owes 15–20% of its day‐to‐day variability to atmospheric forcing. Therefore, atmosphere‐ionosphere coupling is an important source of space weather. The four‐peaked wave‐like longitudinal structure (WN4) in ionosphere is one of the most representative evidence of atmospheric forcing. Studying its characteristics can help us to know more about the coupling mechanism and how the ionosphere responds to different atmospheric waves. We develop a new method to interpret the atmospheric contributions in WN4 of the equatorial total electron content (TEC) directly and quantitatively. The present results confirm former suggestions that zonal DE3 (diurnal, eastward, and zonal wave number 3) is the primary source for WN4. Other waves play a secondary role with respective maxima no more than 2% of the zonal daily mean ITEC (equatorial integrated TEC). Compared with the former method, this method can additionally derive the variation of the background ionosphere modulation, which may give us some insight about the role ionosphere plays in the coupling process. The amplitude of the modulation effect obtains a variation very similar to that of the background ITEC. The phase velocity of the modulation effect is westward during daytime and reverses in the nighttime, indicating the effect caused by the zonal drift of background plasma. Key Points: A new method to quantify tidal and planetary wave contributions in ionospheric WN4 was proposed This approach attempts to derive the background modulated diurnal variation and coupling efficiency Contributions by different tides/PW of both wind components were quantified and evaluated